Gynecological cancers in developing countries: the challenge of chemotherapy in low-resources setting. Issue 4 (1st July 2006) - Basile, S.; Angioli, R.; Manci, N.; Palaia, I.; Plotti, F.; Benedetti Panici, P.
Abstract : The epidemiologic pattern of cancers in developing countries differs in many aspects from that of industrialized nations. Cancer natural history, microbiologic environment, patient's immune system, and drug availability may differ as well. Four of five new cases of cervical cancer and most of cervical cancer deaths occur in developing countries. Where chemoradiation and supportive care facilities are unavailable, it would be logical to consider an inexpensive effective drug. In locally advanced cases, neoadjuvant chemotherapy followed by surgery should be considered the treatment of choice. For ovarian cancer, it may be reasonable to maintain a secure supply of platinum and/or taxanes. For endometrial cancer, platinum compounds are proved active chemotherapic single agents. Oral medroxyprogesterone acetate (MPA) may represent a good chance for treating an advanced or recurrent disease. For vulvar/vaginal cancer, the role of chemotherapy alone is currently considered limited, and it is mostly used as palliative treatment in advanced or recurrent cases. Whenever possible, standard western chemotherapic regimens should be applied in developing countries as well. When standard therapies are unavailable, drugs of choice should be easily accessible, inexpensive, and effective. The most commonly used drugs are cisplatin, cyclophosphamide, and MPA.